Impact of Capital structure on stock return - Mahato, Jai Kumar (Medha: A Multidisciplinary Journal, 2023)
This study delves into the complex variables that impact investor perceptions and market results by investigating the link between a firm's capital structure and its stock performance. The key to sound financial management is understanding a company's capital structure, which is the mix of stock and debt used to finance operations. Considerations include financial risk, cost of capital, financial leverage, market circumstances, investor perception, and regulatory framework. All these aspects interact with capital structure decisions and their impact on stock return. With financial risk being both a blessing and a curse, the effect of capital structure on stock returns is complex and multi-faceted. Using debt can increase earnings during good times, but it leaves you exposed during bad times. Decisions on the capital structure affect the cost of capital, which in turn affects the attractiveness of a firm to investors. By fine-tuning the arrangement of the capital structure, one may lower the cost of capital and, maybe, boost stock returns. Considering both the changes made to the capital structure and the company's financial performance is necessary for evaluating overall returns and, more importantly, for determining if "stock returns are sensitive to changes in the structure. To put a number on this effect, we used stock returns as our dependent variable and debt-to-equity ratios, return on equity, and profits per share as our independent variables. The supplied variables were used to produce the findings using the regression model".